A Systematic Review of Dependent Group Contingencies (1970–2019) - Page, Scott V.; Zimmerman, Dylan M.; Pinkelman, Sarah E. (Journal of positive behavior interventions, 2023)
Dependent group contingencies offer an efficient way to improve the behavior of an entire group of students, as the performance of only one or a few students needs to be monitored at a time. Prior literature reviews outlined the use of group contingency interventions with children in educational settings; however, these reviews did not exclusively examine dependent group contingencies or the varied conditions under which this intervention has been implemented. The purpose of this review was to classify the settings, populations, outcome measures, intervention components, and procedural parameters of dependent group contingencies across the research literature. We completed electronic database searches between 1970 and 2019 for experimental studies in APA PsycINFO, ERIC, CINAHL, CINHAL Complete, Psychology and Behavioral Sciences Collection, Education Source, Academic Search Ultimate, and ProQuest and ancestral searches for the exact terms “dependent group contingenc*” OR “dependent group-oriented contingenc*” in the title, abstract, or author-defined keywords. The results of our review are summarized and discussed in terms of directions for future research and implications for practice.